1991
DOI: 10.1016/0304-3959(91)90032-s
|View full text |Cite
|
Sign up to set email alerts
|

Can anxiety help us tolerate pain?

Abstract: It was hypothesized that anxiety which is relevant to the source of pain exacerbates pain, whereas anxiety which is irrelevant to the source of pain reduces the experience of pain. Female subjects were given either high or low anxiety provoking information about a cold pressor task (relevant anxiety) or high or low anxiety provoking information about a potential shock (irrelevant anxiety). Subjects were then exposed to the cold pressor. The results demonstrated that subjects who were highly anxious about the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
2
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(101 citation statements)
references
References 33 publications
2
89
2
8
Order By: Relevance
“…Experimental studies have also confirmed the enhancing effect of anxiety on pain for different components and measures of pain, e.g., ratings of pain intensity [243] and unpleasantness [244] , and pain threshold [245] . However, little is known about the human forebrain mechanisms underlying emotional modulation of pain, especially by anxiety.…”
Section: Anxietymentioning
confidence: 81%
“…Experimental studies have also confirmed the enhancing effect of anxiety on pain for different components and measures of pain, e.g., ratings of pain intensity [243] and unpleasantness [244] , and pain threshold [245] . However, little is known about the human forebrain mechanisms underlying emotional modulation of pain, especially by anxiety.…”
Section: Anxietymentioning
confidence: 81%
“…For example, anxiety levels have been shown to predict pain severity and pain behavior in acute and chronic pain patients (Kain et al, 2000;van den Hout et al, 2001), and anxiety reduction techniques and anxiolytic drugs have been reported to be successful in ameliorating pain associated with medical procedures (Suls and Wan, 1989;Dellemijn and Fields, 1994). Experimental studies have confirmed the enhancing effect of anxiety on pain for different components and measures of pain, e.g., ratings of pain intensity (Al Absi and Rokke, 1991) and unpleasantness (Weisenberg et al, 1984), pain threshold (Rhudy and Meagher, 2000), and pain discrimination (Schumacher and Velden, 1984). Anxiolytic drugs reverse the experimental effect (Gracely et al, 1978;Janssen and Arntz, 1999).…”
Section: Abstract: Hyperalgesia; Hippocampus; Classical Fear Conditimentioning
confidence: 90%
“…Chronic stress is also a well-recognised predisposing factor in anxiety disorders and clinical studies have provided evidence that there is high comorbidity between pain and anxiety (Asmundson and Katz, 2009;Atkinson et al, 1991). Furthermore, a persistent anxiety state can exacerbate pain leading to anxietyinduced hyperalgesia (al Absi and Rokke, 1991;Dougher, 1979;Rhudy and Meagher, 2000). Thus, preclinical and clinical studies provide substantial evidence for hyperalgesia associated with chronic stress or anxiety (SIH), but the underlying neuronal mechanisms are still not well understood.…”
Section: Introductionmentioning
confidence: 99%